Application Application of model cooperative learning type numbered head together can improve the achievement of learning mathematics materials KPK and FPB students : Application of model cooperative learning type numbered head together can improve the achievement of learning mathematics materials KPK and FPB students - Umu Fadilah (Journal of diversity in learning (JDIL), 2020)
The problem in this research is how to improve student learning achievement in FPB and KPK materials with the implementation of the NHT model cooperative learning model. This research was conducted at SDN Pangkatrejo II where researchers teach. The subjects of the study were grade IV students of 18 students. NHT, achievement, FPB and KPKLearning with the NHT method on KPK and FPB material has a positive impact in improving student learning achievement which is characterized by increasing student learning completeness every cycle, namely, cycle I 66.7%to 83.3%in cycle II. The application of the NHT method in KPK and FPB subject matter has a positive influence, which is to improve students' skills in solving problems related to KPK and FPB shown by the increasing number of children who can do problems about KPK and FPB well.